Significance and Process of Fraction Concept Comprehension: A Study of Learning Constraints from the Perspective of Mathematics Instructors - Alsulami, Naif Mastoor; Galang Isnawan, Muhamad (Nashir Al-Kutub Indonesia, 2023)
Conversion of mixed numbers into improper fractions was one of the challenging formulaic issues in fraction learning that posed problems in education. However, there were not many studies investigating this conversion. Furthermore, few studies have attempted to provide solutions regarding this conversion issue. Therefore, this study aimed to identify the learning constraints students experienced when converting mixed numbers into improper fractions and offer alternative solutions to minimize these learning obstacles. The research design used to achieve this goal was didactical design research (DDR). DDR was chosen as it employed the identified learning constraints to develop didactic designs in fraction learning. Participants in this study were mathematics teachers aged 26, with less than five years of teaching experience. The primary instrument in this research was the researcher, using several supplementary tools such as a fraction comprehension test, interview guidelines, and didactic designs. Data were subsequently analyzed using qualitative data analysis. The research findings revealed that students were indicated to encounter learning obstacles of an epistemological nature, as they seldom initiated learning with real-life problems. The proposed solution in the didactic design was using problems as initial situations in learning, which would then be responded to by students in the form of didactic conditions. The recommendation offered in this study is implementing the didactic design itself.